Differentiating - Thomas, Ian (Henry Stewart Talks, 2011)
Introduction to differentiation, What is differentiation? Why is it important?, Differentiation as a key source of competitive advantage, Understanding the Product Life Cycle, The difference between being 'different' and being 'differentiated', A 'value curve' of differentiation, Demand and supply side factors, 20 ways to differentiate, 10 key sources which add distinctive values for a customer, 10 additional key marketing actions which will create and reinforce strong differentiation, What difference does differentiation make to price?, Pricing for differentiation, definitions for value, The basics of setting differentiated prices, Conclusion